Analisis Pengaruh Implementasi Talent Management Terhadap Kinerja Laporan Keuangan Pada Penatausahaan Aset Negara Di Kementerian Agama - Ilham Mahatir; Dewi Haryani; Iu Rusliana (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
This study examines the impact of talent management implementation on the performance of financial reporting in the administration of state assets at the Ministry of Religious Affairs. Employing a quantitative research approach, the study investigates the relationship between talent management encompassing planning, development, and talent placement and the quality of financial reporting, evaluated through accuracy, completeness, and timeliness. Data were gathered through Likert-scale questionnaires and financial report documentation, followed by analysis using simple linear regression and t-tests. The findings reveal that talent management significantly enhances financial reporting performance, with an R-squared value of 0.72, indicating that 72% of the variance in financial reporting performance is attributable to effective talent management. The remaining 28% is influenced by external factors. These results highlight the critical role of consistent and integrated talent management practices in driving organizational efficiency and accountability, particularly in the context of state asset administration.